2006
DOI: 10.1097/01.prs.0000185604.15606.e5
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Delays in Children with Deformational Plagiocephaly

Abstract: This study indicates that before any intervention, infants with deformational plagiocephaly show significant delays in both mental and psychomotor development. Also of particular note is that no child with deformational plagiocephaly showed accelerated development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 23 publications
3
36
1
1
Order By: Relevance
“…10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone. However, almost none of these studies account for sleep position and many have problems with their design, suggesting that there are probably other factors at play.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…10,21,28,30,63 Multiple reports over the past decade have pointed to links between PP and abnormal ophthalmological findings, auditory processing, and motor development. 4,10,25,27,28,35,44,47,62,63,68 Two case-controlled studies, by Speltz et al 63 and Fowler et al, 21 found significant variability in gross motor development and body tone. However, almost none of these studies account for sleep position and many have problems with their design, suggesting that there are probably other factors at play.…”
Section: Established Risk Factorsmentioning
confidence: 99%
“…17 Some studies have reported the existence of motor delays and poor head control in infants with plagiocephaly. 1,18 In addition, infants with torticollis are also at increased risk for early gross motor delay. 19 Some studies have used the assessment of the milestone achievement in infants.…”
mentioning
confidence: 99%
“…18,[20][21][22] As might be suspected, conditions that cause delayed or abnormal development may predispose to positional skull deformity (eg, infants with hypotonia or hypertonia). 23,24 Concerns have been raised over vision development 25 and mandibular asymmetry, 26 but a causal link to positional skull deformity has not been established. 16 Likewise, there has been no credible medical evidence to support concerns brought up in lay literature associating positional skull deformity to otitis media, temporomandibular joint (TMJ) syndrome, scoliosis, or hip dislocation.…”
Section: Introductionmentioning
confidence: 99%